Analisis Komparatif Peternak Penggemukan Sapi Mitra dan Non Mitra Pada PT. Great Gaint Lifestock dan Kelompok Limousin - zulkarnain - zulkarnain; Wintari Mandala (Journal of Food System & Agribusiness, 2020)
Animal husbandry plays a strategic role in the development of the agricultural sector which aims to meet the needs of animal protein, empower the economic community, and to trigger regional development. Therefore, it is necessary to increase productivity which has an impact on increasing income. Income is used to assess the success of a business and determine the success of a farming business. The objective of this study was to determine the income differences between partner cattle farmers and non-partner cattle farmers. The research method was a survey method carried out in Astomulyo Village, Punggur District, Central Lampung Regency. The samples of this research were 54 partner farmers and 10 non-partner farmers. The analysis methods used were income analysis, R / C ratio and t test analysis. The results showed that the total income of partner farmers was Rp.28,490,166.67. It was Rp12,755,066.7 lower than non-partner farmers which was Rp.41,245,233.33. From the income analysis, it was found that the ratio of farmer income to the total cost of non-partner farmers was 1.26 and partner farmers with a value of 1.15. Statistically, there is  no significant difference between the selling price of partner and non-partner cattle farmers. Keywords: Partnership, Comparative, Income, Farmer, Rearing, Cattle